Mass Opinions: Globalization and Issues as Axes of Contention - Bernhard Weßels; Oliver Strijbis (The Struggle Over Borders. Cosmopolitanism and Communitarianism, 2019)
This chapter aims to answer two general questions: Is there conflict on certain core issues relating to globalization within societies; and does the context of globalization matter for the strength of this conflict? Results show quite strong aggregate correlations between economic and cultural globalization and support for migration, between political and cultural globalization and support for internationalized governance, and some support for a relationship between problem loads and issue orientations. At the individual level, our results show that educational differences produce strong differences in issue orientations in particular regarding migration and global warming, the higher the level of education, the stronger the support for migration and, to some extent, for border-crossing authority as well, and the higher the sensitivity to environmental problems. Results also show that the contexts of globalization shape the degree how strong differences between social and ideological groups have an impact on issue orientations. Generally, the more globalized a country is, the more polarized opinions are between social and political groups in society.
Keywords: 300; mass opinion; issue orientation; globalization; multi-level analysis; context analysis; politicization